AKAD KAFALAH BI GHAIR UJRAH PADA PENDIDIKAN TAMAN KANAK-KANAK (Studi Kasus Taman Kanak-kanak Aisyiyah Bustanul Athfal 4 Kota Blitar) - Marhardita, Yunita Dasa (Diponegoro Journal of Islamic Economics and Business, 2024)
The kafalah bi ghair ujrah contract is a Sharia financial instrument that involves a guarantee provided by one party on behalf of another without requiring any fees or compensation. As an Islamic-based educational institution, a kindergarten has sought solutions that align with Islamic principles to alleviate the financial burden of education on parents or guardian. One of the solutions implemented is the use of the kafalah bi ghair ujrah contract. This study aims to determine the mechanism for using the kafalah bi ghair ujrah contract in education financing at Aisyiyah Bustanul Athfal 4 Kindergarten in Blitar City. The method used by researchers is qualitative with a case study approach. Data were collected through observation, interviews, and documentation.The results of the study in dicate that the application of the kafalah bi ghair ujrah contract can significantly reduce education costs for parents or guardians of students. On the other hand, this contract also helps schools in improving the quality of education and the sustainability of school operations. In this case, it can be concluded that the kafalah bi ghair ujrah contract is a solution that is in accordance with the rules or principles of sharia, which can be applied to educational institutions to ease the burden of education financing.